Is there a difference in treatment effect of different intra-articular drugs for temporomandibular joint osteoarthritis? A systematic review of randomized controlled trials. Issue 9 (September 2021) - Liapaki, A.; Thamm, J.R.; Ha, S.; Monteiro, J.L.G.C.; McCain, J.P.; Troulis, M.J.; Guastaldi, F.P.S.
Abstract: A systematic review based on the PRISMA guidelines was conducted to investigate and compare treatment with hyaluronic acid (HA), corticosteroids, and blood products in patients with temporomandibular joint osteoarthritis (TMJOA). The MEDLINE/PubMed, Embase, and Cochrane Library databases were searched for articles published until September 25, 2019. Articles met the inclusion criteria if they reported patients with TMJOA, a comparison group, and a follow-up period of at least 6 months. The mean and standard deviation for TMJ pain and maximum mouth opening (MMO) were reported. Nine studies involving 443 patients were included. Injectables and Ringer's lactate solution or normal saline were reported to significantly improve TMJ pain and MMO. Regarding TMJ pain, two studies showed a significant superiority of plasma rich in growth factors (PRGF)/platelet-rich plasma (PRP) injections with or without arthrocentesis over HA, but HA showed a significant improvement compared to corticosteroids. For MMO, no injectable was found to be superior to Ringer's lactate or a normal saline control, but arthrocentesis + PRP resulted in MMO improvement compared to arthrocentesis + HA. Overall, all injectables in conjunction with arthrocentesis were efficient in alleviating pain and improving MMO in TMJOA patients; however, a meta-analysis was not possible due to heterogeneity across studies.